Comparative efficacy of traditional non-pharmacological add-on treatments in patients with stable chronic obstructive pulmonary disease: a systematic review and network meta-analysis - Roh, Ji-Ae; Leem, Jungtae; Lee, Beom-Joon; Kim, Kwan-Il; Jung, Hee-Jae (Frontiers in Public Health, 2025)
Chronic obstructive pulmonary disease (COPD) is a major global public health concern. In this study, we examined the comparative efficacy of non-pharmacological interventions within East Asian traditional medicine (EATM-NPI) for enhancing pulmonary function and exercise capacity in patients with stable COPD. A thorough search of electronic databases conducted until May 22, 2022, identified studies employing EATM-NPI in such patients. The evaluation focused on the impact adjunctive therapies on pulmonary function (forced expiratory volume in 1 s [FEV1]) and exercise capacity (6-min walking distance [6MWD]). The qualitative assessment encompassed 142 studies, with 133 studies included in one of three network meta-analyses. Participants, aged 49–76 years, ranged from 9 to 139 per group, predominantly from China (87.7% of studies). Overall study quality was generally low, and reported adverse events were mild. Notably, moxibustion and qigong adjunctive therapies demonstrated significant improvements in FEV1 (L) and FEV1 (%). Additionally, chuna, acupuncture, qigong and moxibustion adjunctive therapies were associated with significant improvements in 6MWD. In conclusion, EATM-NPI adjunctive therapy, when combined with standard pharmacological treatment, exhibited effects on pulmonary function and exercise capacity in patients with COPD.Systematic review registration: The protocol was registered with PROSPERO (CRD42023389431), https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023389431.